2016
DOI: 10.1016/j.eml.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-dependent load transfer governs the strength and failure mechanism of carbon nanotube yarns

Abstract: The outstanding properties of individual carbon nanotubes (CNTs) have motivated interest in CNT fibers for composite materials, high-strength conductors and multifunctional textiles. However, despite advances in manufacturing, the strength of CNT fiber remains 10-100 fold less than individual CNTs. In light of the complex, multi-scale load transfer in CNT yarns, a hierarchical model taking into consideration the morphology-dependent mechanics is necessary to understand this limitation. We present a coupled ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Owing to recent advances in characterization and capturing the dynamical friction [35] and inter-tube shear between CNTs represented at the ultra CG level [16,17], the derived mDEM models will be useful for simulating the mechanics of material systems comprising collapsed CNTs obtained by sheet stretching [2]. Recent modeling [36] revealed that bending rigidity of CNTs impacts, among other factors, the strength of CNT yarn, with the more flexible CNTs making stronger yarns. As our DFTB calculations showed, collapsed CNTs present extraordinary flexibility, comparable to that of few-layer graphene.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to recent advances in characterization and capturing the dynamical friction [35] and inter-tube shear between CNTs represented at the ultra CG level [16,17], the derived mDEM models will be useful for simulating the mechanics of material systems comprising collapsed CNTs obtained by sheet stretching [2]. Recent modeling [36] revealed that bending rigidity of CNTs impacts, among other factors, the strength of CNT yarn, with the more flexible CNTs making stronger yarns. As our DFTB calculations showed, collapsed CNTs present extraordinary flexibility, comparable to that of few-layer graphene.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore compare the per-CNT forces shown to influence growth with the strengths of CNT–CNT contacts within the forest. The contact strength between any pair of CNTs within the forest is determined by the local contact area that results from a balance between elastic deformation and vdW adhesion, which is determined by the diameter, wall number, and shape of each CNT . Using a three-dimensional model of the wavy morphology of the CNT forest and analytical calculation of the strength of each contact, we derive the distribution of contact strengths (Figure a) for CNT forests with alignments spanning the range in the force-modulated growth series.…”
Section: Resultsmentioning
confidence: 99%
“…The contact strength between any pair of CNTs within the forest is determined by the local contact area that results from a balance between elastic deformation and vdW adhesion, which is determined by the diameter, wall number, and shape of each CNT. 35 Using a three-dimensional model of the wavy morphology of the CNT forest and analytical calculation of the strength of each contact, 35 we derive the distribution of contact strengths (Figure 7a) for CNT forests with alignments spanning the range in the force-modulated growth series. We find that the contact strength distribution shifts upward with greater vertical alignment of CNTs, because the alignment induces a greater contact area between CNTs.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this communication, by fabricating and studying CNT sheets with deterministic geometry, we were able to apply fracture mechanics principles to explain for the first time the toughening mechanisms of CNT sheets . As a final note, we can demonstrate, how these values can be compared to the mechanical behavior of CNT yarns . For example, CNT yarns are known to dissipate energy in the range of 100 J g −1 for gauge length of 20 mm and 30 μm diameter, and their weight density is in the range of 1 000 kg m −3 .…”
mentioning
confidence: 94%